Manajemen Sistem Informasi Pembelajaran - Adisel Adisel (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine the management of learning information systems. The method used is the literature study method, namely by collecting material, data and information from books, journals and articles relating to the issues discussed. The results of the study, with a good SIM, developers with the implementation of computer-based SIM learning activities can be completed quickly and precisely in order to achieve organizational goals. This is due to the fact that computer-based management information systems have advantages in managing information, namely speed, quantity, repetitive, complexity, high accuracy, and other advantages so that it can support the development of an organization, Conclusions, management information systems can support the development of learning. Keywords: Learning, Management of Information Systems